2022
DOI: 10.48550/arxiv.2203.14270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trace Embeddings from Zero Surgery Homeomorphisms

Abstract: Manolescu and Piccirillo recently initiated a program to construct an exotic S 4 or #nCP 2 by using zero surgery homeomorphisms and Rasmussen's s-invariant [MP21]. They find five knots that if any were slice, one could construct an exotic S 4 and disprove the Smooth 4-dimensional Poincaré conjecture. We rule out this exciting possibility and show that these knots are not slice. To do this, we use a zero surgery homeomorphism to relate slice properties of two knots stably after a connected sum with some 4manifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Remark 1.5. After our paper was posted on the arXiv, Nakamura [41] showed that the knots in Figures 1 and 23 are not H-slice in # 𝑛 ℂℙ 2 for any 𝑛 (and in particular not slice). Thus, they cannot be used to produce an exotic 𝑆 4 or # 𝑛 ℂℙ 2 .…”
Section: Theorem 13 If Any Of the Five Knots Shown In Figurementioning
confidence: 99%
“…Remark 1.5. After our paper was posted on the arXiv, Nakamura [41] showed that the knots in Figures 1 and 23 are not H-slice in # 𝑛 ℂℙ 2 for any 𝑛 (and in particular not slice). Thus, they cannot be used to produce an exotic 𝑆 4 or # 𝑛 ℂℙ 2 .…”
Section: Theorem 13 If Any Of the Five Knots Shown In Figurementioning
confidence: 99%